Involvement of secretory phospholipase A2 activity in the zymosan rat air pouch model of inflammation. - Payá, M. (1996)
1. In the zymosan rat air pouch model of inflammation we have assessed the time dependence of phospholipase A2 (PLA2) accumulation in the inflammatory exudates as well as cell migration, myeloperoxidase activity, prostaglandin E2 (PGE2) and leukotriene B4 (LTB4) levels. 2. A significant increase in PLA2 activity was detected in 1,200 g supernatants of exudates 8 h after injection of zymosan into rat air pouch. This event coincided with peaks in cell accumulation (mainly neutrophils) and myeloperoxidase activity in exudates and was preceded by a rise in eicosanoid levels. 3. This enzyme (without further purification) behaved as a secretory type II PLA2 with an optimum pH at 7-8 units, lack of selectivity for arachidonate release and dependence on mM calcium concentrations for maximal activity. 4. The PLA2 inhibitors manoalide and scalaradial inhibited this enzyme activity in vitro in a concentration-dependent manner. Scalaradial also inhibited zymosan stimulated myeloperoxidase release in vitro. 5. Injection of the marine PLA2 inhibitor scalaradial together with zymosan into the pouch at doses of 0.5, 1 and 5 mumol per pouch resulted in a dose-dependent inhibition of PLA2 activity in exudates collected 8 h later. Myeloperoxidase levels and cell migration were also decreased, while eicosanoid levels were not modified. 6. Colchicine administration to rats prevented infiltration and decreased PLA2 levels in the 8 h zymosan-injected air pouch. 7. These results indicate that during inflammatory response to zymosan in the rat air pouch a secretory PLA2 activity is released into the exudates. The source of this activity is mainly the neutrophil which migrates into the pouch. 8. Scalaradial exerts anti-inflammatory effects in the zymosan air pouch.